1967
DOI: 10.1128/aem.15.6.1479-1482.1967
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Supplemental Calcium or Calcium-binding Agents on Staphylococcal Bacteriophage Proliferation in Skim Milk1

Abstract: Additions of 0.0005 N calcium borogluconate to Trypticase Soy Broth (TSB) produced an increase in phage titer about 1 million-fold, whereas its addition to skim milk resulted in about a 100-fold decrease in the maximal titer. Supplemental calcium had a stimulatory influence on bacterial growth in TSB but not in skim milk. Studies were made of the effect of binding of calcium of skim milk on the proliferation of staphylococcal bacteriophage. Sequestering the calcium with 2% phosphate mixture inactivated the pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2008
2008

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…The role of inorganic cations (Ca 2+ and Mg 2+ ) in cell lysis is noteworthy. It was observed that chelating agents are able to inhibit bacteriophage proliferation by binding divalent cations (Shafia and Thompson 1964; Das and Marshal 1967; Sadashiva Karnik and Gopinathan 1980; Hicks and Surjawan 2002; Suárez et al. 2007), interfering with phage adsorption (Lorenz et al.…”
Section: Discussionmentioning
confidence: 99%
“…The role of inorganic cations (Ca 2+ and Mg 2+ ) in cell lysis is noteworthy. It was observed that chelating agents are able to inhibit bacteriophage proliferation by binding divalent cations (Shafia and Thompson 1964; Das and Marshal 1967; Sadashiva Karnik and Gopinathan 1980; Hicks and Surjawan 2002; Suárez et al. 2007), interfering with phage adsorption (Lorenz et al.…”
Section: Discussionmentioning
confidence: 99%